Why does caste still influence access to agricultural credit? - Sunil Mitra Kumar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In India, caste shapes access to a variety of resources and outcomes mainly through its influence on inter-generational prosperity, but also the linked phenomenon of discrimination. This paper examines whether caste-based differences in access to formal agricultural loans reflect discrimination in banks' lending. We find, first, that there are significant caste-based differences in loan application rates. Having controlled for the decision to seek credit and various borrower characteristics, we also find that loan approval rates across castes are largely equal across three of four caste-groups, but that Scheduled Tribe (ST) borrowers are less likely to have loans approved. Through a simulation-based approach, we show that these lower approval rates for STs are most likely not explained by unobserved credit histories, suggesting that banks do discriminate against STs. We discuss the policy implications that arise from these findings
Keywords: C15; E51; G21; J15; O12; Z13; 330; caste; rural bank credit; discrimination; simulation; India